The utilizing of control chart in cusmonitoring in a hospitaltomer satisfaction score - M Farahbakhsh; A Nikniaz; A Mardi; A Hasan Zade; S Entezar (Tehran University of Medical Sciences, 2013)
Background: utilizing control chart in customer satisfaction evaluation is one of the effective tools in making results of customer analysis practical. This study was conducted to design the method of utilizing control chart in monitoring customer satisfaction in health care facilities.This prospective study measured service recipients' satisfaction in a three month period in a public hospital using a questionnaire in likert scale. After gathering initial data they were analyzed using SPSS and Excel soft wares .In order to evaluate customer satisfaction a ten parameter checklist and interview was used. The average and standard deviation of decuple and quintuple subgroups were compared.Results: In a three month period the average patient satisfaction score was 4.5 in likert 5 score scale.There wasn't a significant statistical difference between 5,10,25 day duration in patient satisfaction. In addition there wasn't significant statistical difference between 5 samples per day and 10 samples per day and all samples in a day. R-X diagram was used for PSS monitoring.Conclusion: The results of this study showed that the average PSS in 20 and 25 day periods had no significant difference with 3 month PSS and also there wasn't significant statistical difference between average PSS in decuple and quintuple subgroups.